Conceptualising employee involvement in service innovation: an integrative review. (29th July 2021) - Engen, Marit; Fuglsang, Lars; Tuominen, Tiina; Sundbo, Jon; Møller, Jørn Kjølseth; Scupola, Ada; Sørensen, Flemming
Abstract : Purpose: Employees are considered as important contributors to service innovation, but the literature is not unanimous about what employee involvement in service innovation entails. To advance theoretical understanding of the topic, this paper develops a conceptual framework for analysing employee involvement in service innovations, reviews existing research on the topic and proposes a research agenda. Design/methodology/approach: Different modes of employee involvement in service innovation are distinguished based on two dimensions: (1) the intensity of employee influence on service innovation and (2) the breadth of the innovation activity in which employees are involved. This conceptual framework is abductively developed through a literature review of empirical service innovation studies to identify and analyse whether and how these modes of employee involvement are manifested in the service innovation literature. Findings: The findings delineate six modes of employee involvement in the reviewed service innovation studies. Employees are primarily seen as having a strong influence on situated innovation activities but a limited influence on systemic innovation activities. The findings show that more research is needed to assess the connections between different modes of employee involvement. Practical implications: The findings can be used by practitioners to assess the possibilities different modes of employee involvement may bring to service innovation activities. Originality/value: The proposed conceptual framework and the analysis of current research and research gaps in service innovation studies provide a clear research agenda for progressing multidimensional understanding of employee involvement in service innovation.